1997
DOI: 10.1007/pl00009512
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngo-Esophageal Dysphagia in Parkinson's Disease

Abstract: The radiologic characteristics of pharyngoesophageal (PE) dysfunction in Parkinson's disease (PD) are not well established, partly because most previous studies have examined only small numbers of patients. We administered a dynamic videofluoroscopic swallowing function study to 71 patients with idiopathic PD. Using the Hoehn and Yahr disease severity scale, patients were subdivided into those with mild/moderate disease, subgroup I (n = 38), and advanced PD disease, subgroup II (n = 33). From pharyngeal ingest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
108
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(118 citation statements)
references
References 57 publications
7
108
0
3
Order By: Relevance
“…However, in an earlier study it was shown that aspiration is evident mainly in the later stages of the disease (29), and the latency of the onset of dysphagia might be up to 130 months (10 yrs) after onset of PD (30). The patients in the present study were on the verge of this latency time, and hence may not yet have manifested such problems as aspiration.…”
Section: Discussionmentioning
confidence: 45%
“…However, in an earlier study it was shown that aspiration is evident mainly in the later stages of the disease (29), and the latency of the onset of dysphagia might be up to 130 months (10 yrs) after onset of PD (30). The patients in the present study were on the verge of this latency time, and hence may not yet have manifested such problems as aspiration.…”
Section: Discussionmentioning
confidence: 45%
“…Swallowing dysfunction in PD patients covers the clinical area from mild dysphagia to life threatening aspiration-induced pneumonias (7)(8)(9). The cause of swallowing dysfunction is often not known for PD patients, but a dysfunctional regulation pattern in the medulla oblongata (10) has been speculated (11).…”
Section: Introductionmentioning
confidence: 99%
“…The nasal cavity (in humans) is divided in to two symmetrical halves by a septum with each cavity sub-dived into four areas namely vestibules, atrium, respiratory region and olfactory regions. With a surface area of 150 cm 2 , total volume of 15-20 mL the nasal cavity provides an optimal absorption area for drugs into the systemic circulations which would inevitably enhance the bioavailability of the therapeutic agent, particularly those which demonstrate poor oral absorption (intestinal permeation) or significant first-pass metabolism (extra-hepatic and hepatic) 5,6 . Although originally exploited for the delivery of locally acting agents (allergic of infections rhinitis, nasal pluposos and sinusitis) the highly vascularised nature of the nasal cavity has provided a portal for systemic delivery of small molecules and biomolecules 7 .…”
Section: Introductionmentioning
confidence: 99%